Anthocyanins from a single botanical source can be used as a replacement for hemalum and eosin. (17th November 2021) - Alshamar, Hayfaa A.; Dapson, Richard W.
ABSTRACT: For various reasons, histologists in several parts of the world have tried to replace hematoxylin and eosin with locally available plant dyes of the anthocyanin family. Blue or violet nuclear stains have been created by combining an anthocyanin with iron or aluminum ions at low pH. Obtaining a pink or red cytoplasmic counterstain, however, has not been achieved previously, even with a red solution of anthocyanin, because the chemistry of the colorant does not allow bonding to cytoplasmic materials and collagen. We used two extracts from the petals of common mallow, Malva sylvestris, to create both a blue nuclear stain and a red counterstain. The two extracts contained two chemically distinct types of anthocyanins. The first extract contains vic -hydroxyls capable of complexing aluminum ions; its flavylium core is cationic. The second type lacks vic -hydroxyls on its core structure, but includes pendant glucosides that contain a malonic acid ester with a free carboxyl substituent. The precise identity of the first anthocyanin currently is unknown, but likely is one or more of the common anthocyanins such as cyanidin, delphinidin or petunidin, which complex readily with aluminum. The second anthocyanin is malonated malvidin, which does not complex with aluminum, but is anionic at the pH used here. The overall visual effect of applying the two anthocyanin extracts is remarkably similar to that of hemalum plus eosin.